Impact of dispersant on early life stages of the water flea Daphnia magna and the eastern oyster Crassostrea virginica. Issue 12 (27th June 2017) - Salehi, Maryam; Rodriguez, Rachel; Boettcher, Anne; Powers, Sean; Geitner, Nick; Ladner, David A.; Rikard, Scott; Whelton, Andrew J.
Abstract: In response to the 2010 Deepwater Horizon oil spill, over 1 million gallons of dispersant were applied in Gulf of Mexico offshore waters; Corexit 9500 was the most applied dispersant. The impact on organisms in nearshore and freshwaters has received little scrutiny. Acute 48 h toxicity of Corexit 9500 and a new hyperbranched polyethylenimine (HPEI) dispersant‐like compound were evaluated for the freshwater indicator organism, Daphnia magna and for larval and early spat stages of the Eastern oyster, Crassostrea virginica . For D. magna, Corexit 9500 demonstrated toxicity (EC50 of 0.14 [0.13, 0.15] ppm) similar to the 10‐kDa HPEI (EC50 of 0.16 [0.12, 0.19] ppm). HPEI toxicity increased as a function of molecular weight (1.2 to 750 kDa). The 10 kDa size HPEI was further investigated because it dispersed crude oil with equal effectiveness as Corexit. For Corexit, 100% oyster mortality was detected for the ≤0.2‐mm size classes and mortality >50% for the 0.3‐ and 0.7‐mm size classes at the two greatest concentrations (25 and 50 ppm). HPEI (10 kDa) exhibited low mortality rates (<30%) for all concentrations for all oyster size classes except the 0.1‐mm class. Although mortality rates for this size class were up to 60%, mortality was still less than the mortality caused by Corexit 9500. The low toxicity of HPEI polymers for C. virginica in comparison with Corexit 9500 suggests that HPEI polymers warrant further study. Abstract : Corexit 9500 was the most applied dispersant in the 2010 oil spill in the Gulf of Mexico. Acute 48‐h toxicity testing of Corexit 9500 and HPEI polymers was studied on D. magna and C. virginica . Corexit demonstrated toxicity (EC50 of 0.14 ppm) similar to 10‐kDa HPEI (EC50 of 0.16) for D. magna and increased as a function of molecular weight. Corexit was more toxic than 10‐kDa HPEI (>30%) to larval oysters. Lower toxicity of HPEI polymers warrants further study.